THE IMPLEMENTATION OF HOTS IN TEACHINGENGLISHPROCESS AT TENTH GRADE OF MTI PASIA - Sesmiyanti Sesmiyanti; Melyann Melani (Acitya: Journal of Teaching and Education, 2021)
This research was conducted because HOTS is a significant factor in achieving the learning process in accordance with the 2013 curriculum, HOTS is a solution that students become active and participatory in the learning process, teachers not only explain learning in front of the class, but students must be more active to describe the problems that were found during learning, therefore, the researcher wanted to investigate how the HOTS process was implemented in teaching English at X grade of MTI Pasia in the 2019/2020 school year. The purpose of this research to know how the English teacher at X grade of MTI Pasia apply HOTS in Teaching english process, especially in developing productive and receptive skills according to the level of critical thinking.This type of this research was a qualitative descriptive study, the instruments of this study were documentation (document analysis) and observation sheets to collected the data. The subjects in this study was X grade English teachers at MTI Pasia in the 2019/2020 academic year. The results of this study obtained from the document analysis and observation sheets found that, the English teacher at X gradeof MTI pasia did not apply HOTS in teaching English and learning process. The English teacher only applied HOTS to the learning design, it was not apply to the process in learning, this happened not because it was caused by online learning due to COVID 19 pandemic, but it was happened because the teacher did not encourage learning to be effective during thepandemic, the teacher should still be able to improved the learning process using technological advances,even though it was still a long of perfection than face-to-face learning.